Does Leadership Shake-Up and Financial Struggles Drive Auditor Changes? - Boli, Hubertus Ade Resha Raditya; Akbar, Muhammad Azerifki Nuzul (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
This study investigates the influence of management turnover and financial distress on auditor changes. The research employs a purposive sampling method and utilizes secondary data, specifically financial statements and annual reports of companies listed on the Indonesia Stock Exchange from 2018 to 2021. The sample comprises 324 observations from 81 companies in the non-cyclical consumer goods sector. Logistic regression analysis is applied, as the dependent variable is a binary (dummy) variable. The results indicate that neither management turnover nor financial distress significantly affect auditor changes, suggesting that a company’s decision to switch auditors is independent of changes in its board of directors or financial condition. The findings of this study highlight the complexity of auditor change decisions, suggesting that factors beyond management turnover and financial distress may play a more significant role. These results provide valuable insights for regulators, investors, and policymakers in understanding the stability of auditor-client relationships.